Dominant/non-dominant support limb kinematics and approach run parameters in futsal kicking of stationary and rolling ball - Palucci Vieira, Luiz H. [UNESP]; Cunha, Sergio A.; Santiago, Paulo R.; Dos Santos, Paulo C.; Cardenas, Guilherme C. [UNESP]; Barbieri, Ricardo A.; Baptista, André M. [UNESP]; Barbieri, Fabio A. [UNESP] (Edizioni Minerva Medica, 2019)
BACKGROUND: Task constraints and players’ asymmetry influences on lower extremity (i.e. kicking limb) kinematics during futsal instep kicking. However, support limb behavior when shooting in a futsal context was not previously investigated, and its potential role on such discrepant motor outputs is still unclear. Thus, the study aimed to compare kinematic features of the support limb and approach run between kicking a stationary and a rolling ball using dominant and non-dominant limbs. METHODS: Ten futsal players participated (21.88±2.86 years-old, 73.66±4.17 kg and 1.75±0.04 m) and performed kicks (five per limb per condition) with the dominant and non-dominant limbs in stationary and rolling ball conditions. Kinematic analysis comprised determination of support limb angular joint (hip, knee and ankle) displacement and velocity, approach run distance, angle, linear velocity, step length and width, support foot-to-ball distance, ball velocity (120 Hz) and accuracy (60 Hz). RESULTS: Hip adjustments (greater extension) in the support limb when kicking a rolling ball contributed in maintaining similar performance (e.g., ball velocity) to kicking a stationary ball, compensating for the lower approach run velocity and longer support foot to ball distance. Kicking with the non-dominant limb demonstrated a lower approach run velocity and the non-dominant support limb presented different angular motion compared to the dominant support limb in hip (< internal rotation), knee (< flexion), and ankle joints (< plantar flexion), being harmful to performance in both kicking stationary and rolling balls. CONCLUSIONS: Kicking a stationary and rolling ball presented similar performance, but compared to the dominant side, futsal instep kicks performed with the non-dominant support limb induces lower approach run velocity and inefficient angular joint motion, either harmful to performance output.
Keywords: Biomechanical phenomena; Football; Function laterality; Motor skills